Identification and visualisation of possible ancient ocean shoreline on Mars using submeter-resolution Digital Terrain Models - Świąder, Andrzej (Geologos, 2015)
Digital Terrain Models (DTMs) produced from stereoscopic, submeter-resolution High Resolution Imaging Science Experiment (HiRISE) imagery provide a solid basis for all morphometric analyses of the surface of Mars. In view of the fact that a more effective use of DTMs is hindered by complicated and time-consuming manual handling, the automated process provided by specialists of the Ames Intelligent Robotics Group (NASA), Ames Stereo Pipeline, constitutes a good alternative. Four DTMs, covering the global dichotomy boundary between the southern highlands and northern lowlands along the line of the presumable Arabia shoreline, were produced and analysed. One of them included forms that are likely to be indicative of an oceanic basin that extended across the lowland northern hemisphere of Mars in the geological past. The high resolution DTMs obtained were used in the process of landscape visualisation.